Fibrinogen concentrate vs. fresh frozen plasma for the management of coagulopathy during thoraco‐abdominal aortic aneurysm surgery: a pilot randomised controlled trial. (23rd November 2018) - Morrison, G. A.; Koch, J.; Royds, M.; McGee, D.; Chalmers, R. T. A.; Anderson, J.; Nimmo, A. F.
Summary: Major vascular surgery is frequently associated with significant blood loss and coagulopathy. Existing evidence suggests hypofibrinogenaemia develops earlier than other haemostatic deficiencies during major blood loss. The purpose of this study was to assess whether the use of an infusion of fibrinogen concentrate to prevent and treat hypofibrinogenaemia during surgery resulted in satisfactory haemostasis, removing or reducing the need for blood component transfusion. Twenty patients undergoing elective extent‐4 thoraco‐abdominal aortic aneurysm repair were randomly allocated to receive either fresh frozen plasma or fibrinogen concentrate to treat hypofibrinogenaemia during surgery. Coagulation was assessed during and after surgery by point‐of‐care and laboratory testing, respectively, and treatment was guided by pre‐defined transfusion triggers. Despite blood losses of up to 11, 800 ml in the patients who received the fibrinogen concentrate, none required fresh frozen plasma during surgery, and only two required platelet transfusions. The median (IQR [range]) allogeneic blood component administration during surgery and in the first 24 h postoperatively was 22.5 (14–28 [2–41]) units in patients allocated to fresh frozen plasma vs. 4.5 (3–11[0–17]) in patients allocated to fibrinogen concentrate (p = 0.011). All patients in both groups were assessed by the surgeon to have satisfactory haemostasis at the end of surgery. Mean (SD) postoperative fibrinogen concentrations were similar in patients allocated to fresh frozen plasma and fibrinogen concentrate (1.6 (0.3) g.l −1 vs. 1.6 (0.2) g.l −1 ; p = 0.36) but the mean (SD) international normalised ratio and activated partial thromboplastin time ratio were lower in patients allocated to fresh frozen plasma (1.1 (0.1) vs. 1.8 (0.3); p < 0.0001 and 1.1 (0.2) vs. 1.7 (0.5); p = 0.032, respectively). Fibrinogen concentrate may be used as an alternative to fresh frozen plasma in the treatment of coagulopathy during thoraco‐abdominal aortic aneurysm repair.